2017
DOI: 10.1002/2327-6924.12422
|View full text |Cite
|
Sign up to set email alerts
|

State of the evidence

Abstract: Background and purpose Cannabinoids are widely used to alleviate intractable symptoms such as pain, nausea, and muscle spasticity. The purpose of this review was to ascertain the current state of the science regarding use of cannabinoids for cancer pain. Methods Four electronic databases were searched for randomized control trials of cannabinoids and cancer pain. Studies included examined the analgesic effects of cannabinoids for cancer pain. Methodological quality was assessed using the Jadad scale. Conclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 29 publications
0
14
0
2
Order By: Relevance
“…The combination of THC and cannabidiol as a treatment has shown to provide significant pain relief among patients [81]. In a recent systematic review by Tateo [83], from eight low or moderate quality randomized clinical trials, cannabinoids were reported to effectively manage cancer pain when administered in combination with opioid. Nonetheless, further investigations must be carried out on the effectiveness of cannabinoids as adjuvant analgesics.…”
Section: Adjuvant Analgesics In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of THC and cannabidiol as a treatment has shown to provide significant pain relief among patients [81]. In a recent systematic review by Tateo [83], from eight low or moderate quality randomized clinical trials, cannabinoids were reported to effectively manage cancer pain when administered in combination with opioid. Nonetheless, further investigations must be carried out on the effectiveness of cannabinoids as adjuvant analgesics.…”
Section: Adjuvant Analgesics In Cancermentioning
confidence: 99%
“…Nonetheless, further investigations must be carried out on the effectiveness of cannabinoids as adjuvant analgesics. There is no clear evidence that cannabinoids are beneficial for the treatment of cancer pain [80,83,84,85].…”
Section: Adjuvant Analgesics In Cancermentioning
confidence: 99%
“…Even when the analgesic effects from NIB were apparent, the frequency and severity of side effects made the medicine useless. Pain intensity worsened in patients administered BPP [61].…”
Section: The Medical Indications For Cannabinoidsmentioning
confidence: 99%
“…The analgesic effect of THC is, at least in part, mediated through delta and kappa opioid receptors, indicating an intimate connection between cannabinoid and opioid signaling pathways in the modulation of pain perception [62]. In conclusion of the review above, there was low evidence that cannabinoids were effective adjuvants for cancer pain not completely relieved by opioid therapy, and they appeared to be safe in low and medium doses [61].…”
Section: The Medical Indications For Cannabinoidsmentioning
confidence: 99%
“…Recent developments in legalization of cannabis or cannabinoid products has increased interest in these compounds as an alternative therapy for pain. Systemic administration of exogenous cannabinoids to control pain appears to be most efficacious in patients with cancer-related pain (Tateo, 2017 ). The capacity of cannabinoids to decrease nausea and pain in cancer patients has been described by multiple authors, albeit often in the presence of side effects relating to altered mentation (Johnson et al, 2010 ; Abrams and Guzman, 2015 ; Davis, 2016 ).…”
Section: Introductionmentioning
confidence: 99%